PENGARUH MEDIA POP UP FLASHCARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA TK B - Dwi Nurfitria Bella (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2019)
This research is aimed to figure out the comparison of initial reading ability from group B of KSPA UNJ play group Rawamangun. Whether using Pop Up Flashcard media or without using any media to be given. This research type is Pre-Experimental One-Group Pretest Design with 10 subjects. The data collected through pre test and post test while the learning is in progress. Pre test and post test are used to determine the initial reading ability of the students. Furthermore, the data were analyzed by giving pre test hypothesis (normality test and variance homogeneity test) and hypothesis test by using partial test (T). The result are; there is a comparison of the initial reading ability from the group B KSPA UNJ play group when Pop Up Flashcard media was interfered. It also indicates that Ho was rejected and H1 was accepted.